The Metaphilosophy of Eugenio Trías - Caro Rey, Jonatan (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The article is an interpretation of the Metaphilosophy of Eugenio Trías as the liberation of one’s identity (as opposed to subjectivism), and which is parallel to the liberation on the discourse of metaphysics (opposite to the anti metaphysical attitudes of Orthodox —Marxist theories— ideologies and logical positivism). The intimate relationship of this topic in two of his works will be analyzed, and which are not usually associated with the metaphilosophy of Trías, for instance, Philosophy and Carnivals (with a proposal for the conception of identity, such as the abundance of masks and of sociability, as Carnival) and Dispersion (from his fragmentary, aphoristic thought). Both works would respond to the same strategy termed by Trías as "magical", and in this article (as is elucidated at the end) as "cynical".
Keywords: metaphilosophy; liberation; identity; metaphysics; magic; cynicism.